PRIMARY SJOGREN'S SYNDROME ANDOFDISEASE BASEDOV (FAMILY CASE) - M S Panchovska; J I Sheitanov; R M Stoilov; F G Martinova; K. G. Nikolaev (Научно-практическая ревматология)
Bstract. Case report of two sislers with primary Sjttgren’s syndrome combined with Basedow’s disease is described. Immunological studies revealed HLA-DR3 antigen which reliably more often is found in pts with above autoimmunic diseases. Some clinical peculiarities of the process of SjOgrcn’s syndrome stipulated by genetic and exogenous factors.